2020
DOI: 10.3390/molecules25235555
|View full text |Cite
|
Sign up to set email alerts
|

Bergenia Genus: Traditional Uses, Phytochemistry and Pharmacology

Abstract: Bergenia (Saxifragaceae) genus is native to central Asia and encompasses 32 known species. Among these, nine are of pharmacological relevance. In the Indian system of traditional medicine (Ayurveda), “Pashanabheda” (stone breaker) is an elite drug formulation obtained from the rhizomes of B. ligulata. Bergenia species also possess several other biological activities like diuretic, antidiabetic, antitussive, insecticidal, anti-inflammatory, antipyretic, anti-bradykinin, antiviral, antibacterial, antimalarial, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…In various studies, it is revealed that arbutin formulations can be useful for the treatment of various diseases due to its multi‐target biological effects such as treatment of hyperpigmentation disorders (Ayumi, Sahudin, Hussain, Hussain, & Samah, 2019; Park et al, 2019), anti‐diabetic (Lv et al, 2019), wound healing (Polouliakh et al, 2020), anti‐osteoporosis (Bonifacio et al, 2020), treatment of acute lung injury (Ye et al, 2019), management of cardiac hypertrophy (Nalban et al, 2020), anticancer (Jiang et al, 2018; Safari et al, 2020; Wang, Wang, Li, Zhang, & Wang, 2020), antioxidant activity (Bonifacio et al, 2020), treatment of optic nerve injury (Ebrahim‐Tabar, Nazari, Pouramir, Ashrafpour, & Pourabdolhossein, 2020; Zhao, Wang, Qin, & Wang, 2019), treatment of central nervous system disorders (Ahmadian, Ghasemi‐Kasman, Pouramir, & Sadeghi, 2019; Dastan et al, 2019; Ding et al, 2020), hepatoprotective activity (Mirshahvalad et al, 2016), effect on human mesenchymal stem cells (Bonifacio et al, 2020; Jamil, Crowe, Tablin, & Oliver, 2005), radioprotective effect (Nadi, Elahi, Moradi, & Banaei, 2019), antimicrobial (Nadi et al, 2019), antiaging (Zhou et al, 2017), antitussive (Koul, Kumar, Yadav, & Jin, 2020), diuretic (Myagchilov, Mineev, Sokolova, Gerdasova, & Gorovoi, 2020), anti‐inflammatory (Lee & Kim, 2012; Zhou, Zhao, Li, & Reetz, 2019), inhibitory effects on melanin formation (Li, Du, & Du, 2018), estrogen‐like effects (Zeng et al, 2018), and cytoprotective effects (Seyfizadeh et al, 2012) etc.…”
Section: Chemical Characterizations and Therapeutic Effects Of Arbutin In Cosmetic And Pharmaceutical Preparationsmentioning
confidence: 99%
“…In various studies, it is revealed that arbutin formulations can be useful for the treatment of various diseases due to its multi‐target biological effects such as treatment of hyperpigmentation disorders (Ayumi, Sahudin, Hussain, Hussain, & Samah, 2019; Park et al, 2019), anti‐diabetic (Lv et al, 2019), wound healing (Polouliakh et al, 2020), anti‐osteoporosis (Bonifacio et al, 2020), treatment of acute lung injury (Ye et al, 2019), management of cardiac hypertrophy (Nalban et al, 2020), anticancer (Jiang et al, 2018; Safari et al, 2020; Wang, Wang, Li, Zhang, & Wang, 2020), antioxidant activity (Bonifacio et al, 2020), treatment of optic nerve injury (Ebrahim‐Tabar, Nazari, Pouramir, Ashrafpour, & Pourabdolhossein, 2020; Zhao, Wang, Qin, & Wang, 2019), treatment of central nervous system disorders (Ahmadian, Ghasemi‐Kasman, Pouramir, & Sadeghi, 2019; Dastan et al, 2019; Ding et al, 2020), hepatoprotective activity (Mirshahvalad et al, 2016), effect on human mesenchymal stem cells (Bonifacio et al, 2020; Jamil, Crowe, Tablin, & Oliver, 2005), radioprotective effect (Nadi, Elahi, Moradi, & Banaei, 2019), antimicrobial (Nadi et al, 2019), antiaging (Zhou et al, 2017), antitussive (Koul, Kumar, Yadav, & Jin, 2020), diuretic (Myagchilov, Mineev, Sokolova, Gerdasova, & Gorovoi, 2020), anti‐inflammatory (Lee & Kim, 2012; Zhou, Zhao, Li, & Reetz, 2019), inhibitory effects on melanin formation (Li, Du, & Du, 2018), estrogen‐like effects (Zeng et al, 2018), and cytoprotective effects (Seyfizadeh et al, 2012) etc.…”
Section: Chemical Characterizations and Therapeutic Effects Of Arbutin In Cosmetic And Pharmaceutical Preparationsmentioning
confidence: 99%
“…6–8 In the course of our continuous efforts on exploring traditional Indian flora, we have isolated and identified bergenin ( 5 ) as a major lead phytochemical from fruits of Mallotus philippensis which is reported to have versatile biological activities including anticancer, anti-hepatotoxic, antioxidant, anti-HIV, anti-inflammatory and neuroprotective properties. 9,10 Moreover, recent studies also have demonstrated that bergenin can induce apoptosis by regulating the AKT signaling pathway in human bladder cancer. 11 Despite the wide biological activities, bergenin has poor solubility with weak permeation leading to low absorption and poor bioavailability, 12 which attracted medicinal chemists to focus on its structural modifications to enhance their physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…23 Aerial part of this plant also contains bergenin along with other glycosides and flavonoids. 24 Antiurolithic, anticancer, antimicrobial, antioxidant, antidiabetic and anti-tussive effects have been investigated for this plant. [25][26][27][28] Silver nanoparticles prepared from aqueous extract of Bergenia ciliata rhizomes have shown anticancer potential via inhibition of protein kinase activity.…”
Section: Introductionmentioning
confidence: 99%